The bureaucratic record of merit: moral conditions and loyalty. A study of the personal files of the commanders in chief of the argentine navy (1955-1983) - Barragán Sáez, Ivonne (Revista de Historia Social y de las Mentalidades, 2024)
This article examines the personal files of the commanders-in-chief of the Argentine Navy from 1955 to 1983. It begins by summarizing the attributes, individual qualities, and behaviours valued by the institution and identifies the appointments that facilitated their rise to the highest positions within the force. Simultaneously, it explores the bureaucratic genealogy of these processes by reconstructing the methods used to regulate and document the professional careers of naval officers and the categories employed for this purpose. The analysis is based on an original documentary corpus—comprising the files on the performance and service of fourteen commanders—which has not been previously subjected to systematic study. The findings challenge the public image of internal unity and political homogeneity projected by the Navy, highlighting the strict control exercised by its leadership over senior officers and the solid institutional culture built around the admiralty
Keywords: Argentina; Navy; Files; Trayectories; Commanders